A New Iterative Procedure for the Missing-Value Problem (Journal of Computational Mathematics, 1984)
For a missing-value problem in linear models, all the iterative procedures employed up to now are entirely within the framework of the EM algorithm. This paper proposes a new iterative procedure which is not the EM algorithm in the most general case. In the procedure nothing is assumed about the error distribution in the proof of its convergence. The convergence rate is also obtained.